Atrial cardiomyocytes development from human induced pluripotent stem cells - Yuan, M (2018)
Cardiovascular diseases are the leading cause of death around the globe. Despite ongoing progress, a shortage in the primary source of human cardiac tissue still presents a major limiting factor in relevant research. Human induced pluripotent stem cells (iPSCs) hold great promise in cardiovascular disease mechanistic research and treatment as they can provide an unlimited supply of cardiomyocytes. Nevertheless, so far, the cardiomyocytes derived from human iPSCs disproportionately recapitulated immature ventricular characteristics, which has hindered the application of iPSC-based models in studying atrial-specific diseases and developing relevant therapies. In the current study, the effectiveness of a combined treatment of Gremlin 2 and retinoic acid (RA) in directing atrial cardiomyocyte differentiation from human iPSCs and driving the in vitro maturation of those derived cardiomyocytes was explored. Morphologically, human iPSC-derived cardiomyocytes treated with Gremlin 2 and RA recapitulated human adult atrial cardiomyocyte features. The treated cardiomyocytes showed elevated expressions of cardiac genes, atrial-specific genes, inward rectifier potassium channel coding genes and the β1-adrenergic receptor coding gene. However, no significant differences in gene expressions were identified between the treated cells and untreated cells. In addition, the treated cells displayed increases in calcium transient amplitude after α1- and β- adrenergic stimulations and they showed atrial-type action potentials with mature cardiomyocyte features as well. In conclusion, the above results are insufficient to determine the effectiveness of the combined treatment of Gremlin 2 and RA in directing atrial specification and driving in vitro cell maturation, but evidence has been provided that this treatment combination has the potential to produce mature atrial-type cardiomyocytes from human iPSCs with further optimization.